Identifying and Mitigating Fiscal Risks from State-Owned Enterprises (SOEs). - Ter-Minassian, Teresa (Cuyonomics. Investigaciones en Economía Regional, 2019)
This paper focuses on the fiscal risks created by state-owned enterprises (SOEs). It analyzes the main sources of such risks, in particular flaws in their fiscal, including quasi-fiscal operations; excessive extraction of SOEs resources by their owner governments; preferential access of SOEs to financing; and information asymmetries between the SOEs and their owners. These are illustrated with reference to selected country experiences, mainly in Latin America. Based on this analysis, the paper outlines a number of policy recommendations to identify and mitigate such risks. Este artículo se centra en los riesgos fiscales creados por las empresas estatales. Analiza las principales fuentes de esos riesgos, en particular las fallas en sus operaciones fiscales, incluidas las cuasifiscales; la extracción excesiva de los recursos de las empresas estatales por parte de los gobiernos; el acceso preferencial de estas empresas a la financiación y las asimetrías de información entre ellas y sus propietarios. Todo esto se ejemplifica mediante las experiencias de países seleccionados, principalmente en América Latina. Basado en este análisis, el trabajo describe una serie de recomendaciones de políticas para identificar y mitigar dichos riesgos.